Spatial-temporal evolution of habitat quality in tropical monsoon climate region based on “pattern–process–quality” – a case study of Cambodia - Kang Junmei; Yang Fengshuo; Wang Jun; Liu Yang; Fang Dengmao; Jiang Chengcheng (Open Geosciences)
Exploring the coupling relationship of “pattern–process–quality” is conducive to understanding the internal mechanism of habitat quality change, and is of great significance for the function maintenance and sustainable management of regional ecosystems. Existing studies mainly analyze the spatial-temporal evolution of habitat quality from the perspective of “pattern quality” and land use data. However, the variation in habitat quality is the result of many factors such as “pattern–process–quality” of the habitat. Therefore, it is necessary to consider these factors comprehensively when studying the change in habitat quality, so as to understand the change mechanism of habitat quality more comprehensively and deeply. This study takes Cambodia, a tropical monsoon climate region, as the research area, and uses land cover data from 2000 to 2022 as the data source. InVEST model is used to analyze the spatial-temporal evolution of habitat quality, and explore the relationship between habitat quality and land use, landscape pattern, and ecological process. The results show that (1) during 2000–2022, forest in Cambodia covered a wide range, showing a landscape pattern mainly distributed in the east and west. (2) The degree of fragmentation of impervious landscape pattern increased gradually from 2000 to 2022, indicating that it was seriously affected by human activities and natural factors, and with the increase in elevation and slope, the area of various types converted to impervious decreased. (3) During 2000–2022, high habitat quality areas were concentrated in Tonle SAP Lake in the east, southwest, and central part of Cambodia, while low habitat quality areas were concentrated in the central part. (4) Natural factors, socio-economic factors, policies, and regulations all have an impact on the change in land use pattern and habitat quality in Cambodia.